Effect of Aqueous Extract of Tridax procumbens Linn on Plasma Electrolytes of Salt-Loaded Rats - Jude, Ikewuchi C.; Catherine, Ikewuchi C.; Frank, Onwuka C.; Frank, Onwuka C. (Pakistan Journal of Nutrition, 2010)
The effect of aqueous extract of Tridax procumbens Linn on the weight, packed cell volume and plasma electrolyte profiles of salt-loaded rats were investigated. The test and test-control groups received a diet consisting 8% salt and 92% commercial feed, while the control group received a diet consisting 100% of the commercial feed. The test group also received daily by intra-gastric gavages, 50 mg/100 g body weight of the extract, while the test-control and control groups received appropriate volumes of water by the same route. The mean daily weight gain and Packed Cell Volume (PCV) of the test rats were significantly higher (p